Neovascularized implantable cell homing encapsulation platform with tunable local immunosuppressant delivery for allogeneic cell transplantation. (October 2020) - Paez-Mayorga, Jesus; Capuani, Simone; Hernandez, Nathanael; Farina, Marco; Chua, Corrine Ying Xuan; Blanchard, Ryan; Sizovs, Antons; Liu, Hsuan-Chen; Fraga, Daniel W.; Niles, Jean A.; Salazar, Hector F.; Corradetti, Bruna; et al.
Abstract: Cell encapsulation is an attractive transplantation strategy to treat endocrine disorders. Transplanted cells offer a dynamic and stimulus-responsive system that secretes therapeutics based on patient need. Despite significant advancements, a challenge in allogeneic cell encapsulation is maintaining sufficient oxygen and nutrient exchange, while providing protection from the host immune system. To this end, we developed a subcutaneously implantable dual-reservoir encapsulation system integrating in situ prevascularization and local immunosuppressant delivery, termed NICHE. NICHE structure is 3D-printed in biocompatible polyamide 2200 and comprises of independent cell and drug reservoirs separated by a nanoporous membrane for sustained local release of immunosuppressant. Here we present the development and characterization of NICHE, as well as efficacy validation for allogeneic cell transplantation in an immunocompetent rat model. We established biocompatibility and mechanical stability of NICHE. Further, NICHE vascularization was achieved with the aid of mesenchymal stem cells. Our study demonstrated sustained local elution of immunosuppressant (CTLA4Ig) into the cell reservoir protected transcutaneously-transplanted allogeneic Leydig cells from host immune destruction during a 31-day study, and reduced systemic drug exposure by 12-fold. In summary, NICHE is the first encapsulation platform achieving both in situ vascularization and immunosuppressant delivery, presenting a viable strategy for allogeneic cell transplantation. Highlights: NICHE is a vascularized cell encapsulation platform with local immunosuppression. Vascularization of the cell reservoir was driven by mesenchymal stem cells. Local immunosuppressant delivery (CTLA4Ig) maintained allogeneic cell viability. Local delivery confined drug at the transplant site, limiting systemic exposure. Subcutaneous implantation permits minimally invasive NICHE cell and drug refilling.